2014
DOI: 10.1016/j.psyneuen.2014.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptors in the nucleus of the solitary tract (NTS) decrease endocrine and behavioral stress responses

Abstract: Stress activates the hypothalamo-pituitary-adrenal (HPA) axis, leading to adrenocortical secretion of glucocorticoids. The magnitude and duration of the HPA axis response is mediated in large part by the glucocorticoid receptor (GR). The nucleus of the solitary tract (NTS) abundantly expresses the GR and is a key brain region for processing autonomic and endocrine stress responses. This study tests the hypothesis that GR within the NTS plays an important role in inhibiting stress-induced endocrine and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Jakovcevski et al (2011) reported that acute administration of the less selective GR antagonist mifepristone reduced stressor-induced HPA axis activation and anxiety-like behavior in mice with high trait anxiety, but not in mice with low trait anxiety. The present findings, and those of Jakovcevski et al (2011) may well demonstrate dysregulation of HPA feedback moderating CORT release, particularly in brain regions known to produce regulatory feedback to the paraventricular nucleus of the hypothalamus, such as the nucleus of the solitary tract (Ghosal et al 2014). Thus, the present findings may suggest that acute antagonism of GRs can moderate the severity of affective disruption and activation of the stress axis during ethanol withdrawal.…”
Section: Discussionsupporting
confidence: 61%
“…Jakovcevski et al (2011) reported that acute administration of the less selective GR antagonist mifepristone reduced stressor-induced HPA axis activation and anxiety-like behavior in mice with high trait anxiety, but not in mice with low trait anxiety. The present findings, and those of Jakovcevski et al (2011) may well demonstrate dysregulation of HPA feedback moderating CORT release, particularly in brain regions known to produce regulatory feedback to the paraventricular nucleus of the hypothalamus, such as the nucleus of the solitary tract (Ghosal et al 2014). Thus, the present findings may suggest that acute antagonism of GRs can moderate the severity of affective disruption and activation of the stress axis during ethanol withdrawal.…”
Section: Discussionsupporting
confidence: 61%
“…Lentiviral knockdown of GR in the IL (but not prelimbic cortex) produces a marked potentiation of HPA axis and PVN Fos induction to a novel stress in animals exposed to CVS (91), a phenomenon linked to interneuron-mediated decreases in IL output (92). Implants of the GR antagonist mifepristone in the NTS inhibit PVN excitability following chronic stress, suggesting that the glucocorticoids may play a role in inhibiting the NTS drive to the PVN (93). These data implicate both regions as sites of glucocorticoid feedback (perhaps at the genomic level) and suggest that they function to set HPA reactivity consequent to chronic stress.…”
Section: Chronic Stress and Pvn Afferentsmentioning
confidence: 99%
“…In addition to sending projections that target subcortical limbic regions critical for regulating behavioral responses to stress, the NTS also receives direct input from the amygdala, BST, and prefrontal cortex (van der Kooy et al, 1984). Consequently, the NTS has been implicated in behaviors related to anxiety, depression, and fear memory (Ghosal et al, 2014; Miyashita and Williams, 2002). …”
Section: Nucleus Of the Solitary Tract (Nts)mentioning
confidence: 99%